1998
DOI: 10.1074/jbc.273.7.4275
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of Argos Structure-Function

Abstract: The Drosophila Argos protein is the only known extracellular inhibitor of the epidermal growth factor receptor (EGFR). It is structurally related to the activating ligands, in that it is a secreted protein with a single epidermal growth factor (EGF) domain. To understand the mechanism of Argos inhibition, we have investigated which regions of the protein are essential. A series of deletions were made and tested in vivo; furthermore, by analyzing chimeric proteins between Argos and the activating ligand, Spitz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 62 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Consistent with its role as an inhibitor of dEGFR signaling, Aos knock-outs exhibit phenotypes typical of dEGFR gain-of-function mutants, and Aos misexpression inhibits dEGFR signaling (26,29). Aos contributes importantly to the spatio-temporal regulation of dEGFR signaling through its participation in a negative feedback loop as a result of Spi-dependent dEGFR signaling.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…Consistent with its role as an inhibitor of dEGFR signaling, Aos knock-outs exhibit phenotypes typical of dEGFR gain-of-function mutants, and Aos misexpression inhibits dEGFR signaling (26,29). Aos contributes importantly to the spatio-temporal regulation of dEGFR signaling through its participation in a negative feedback loop as a result of Spi-dependent dEGFR signaling.…”
mentioning
confidence: 82%
“…However, recent studies have shown that Aos inhibits dEGFR signaling by binding to the activating ligand Spi rather than associating with the receptor itself (25), bringing the significance of the atypical EGF-like domain in Aos into question. As pointed out by Howes et al (26), sequences outside the putative EGF motif of Aos are strongly conserved in the house fly Musca domestica (representing an evolutionary distance of ϳ100 million years) and are required for Aos function in vivo, further suggesting that more than just the putative EGF-like domain is required for Aos function. We have expanded upon these observations by identifying Aos orthologs outside the dipteran lineage (Fig.…”
Section: Isolation Of Mutations Affectingmentioning
confidence: 97%
See 3 more Smart Citations